STUDI DESKRIPTIF TENTANG GAYA KEPEMIMPINAN MANAGER OPERASIONAL PT. BANK “X” CABANG PAMANUKAN - Lisa W; Wilma Wirachmaria Sari (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
This research aims to describe leadership style on operational unit of PT Bank X using perception survey toward leadership style based on Hersey and Blancard thery. Having 22 participants, the results shows that 40,91% employee give perception of their leader having telling style. Meanwhile, 27,27% participants give perception about their leaer having selling style. In addition, 18,18% participants have participating style leader and the last 13,64% leadership perceived as having delegating style.